Ways of optimization of plain gearing; Korus 2004; V. 3 - Belyaev D. V. Dmitry Vladimirovich (2004, 2004)
Gearing changes its geometry tooth forms during the exploitation which worsen their qualitative characteristics. Some researches believe [(Blagodarny V, 1985)(Schulz V, 1990)] that worn profile becomes steady and keeps this form during the period of exploitation. As it is noted below, tooth profiles do not degenerate around the pitch point and thus it is impossible to synthesize "worn-out" tooth profiles if they cross the centroide line.